RESPONSIVITAS DAN AKUNTABILITAS PEMERINTAH KOTA UNTUKMENINGKATKAN STATUS KOTA LAYAKANAK - Ramadona, Sarah; Rusli, Zaili; Yuliani, Febri (Jurnal Ilmu Administrasi Negara, 2018)
Responsiveness and Accountability of City Government to Improve the Status of Child-Friendly City. This study aims to determine the implementation of responsiveness and accountability of the City Government to improve the status of Decent City Children. The method used qualitative descriptive approach. Primary data obtained from interviews and observation. Secondary data obtained from data collection with documents. Data analysis uses data collection methods, data reduction, data presentation, and conclusions. The results showed that the responsiveness and accountability of Pekanbaru city government to improve the status of city worthy of children in 2017 is quite optimal This can be seen from the improvement of the fulfillment of children’s rights based on 24 indicators of Decent City Children that have been determined from the Ministry of Women Empowerment and Child Protection.